Analisis Penerapan Model Pendidikan Bagi Anak Yang Mengalami Hambatan Pendengaran Dan Bicara - Rifka Andriani; Shafiah Shafiah; Maizal Efendi; Melisa Putri; Wismanto Wismanto (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Training is one of the functions that can be used to improve human resources. Training can be done in various educational institutions. In the world of education there are classes that are accepted not only students who have normal physical characteristics, but there are also learning schools that accept students who can be called Special Needs Children. Children with special needs can be said to be children who have limitations or differences compared to other normal children. These limitations can be shown through physical, ability, and emotional aspects. This research aims to analyze and suitable education patterns for children who experience special needs. The method used in this research is qualitative research using library research method by collecting data from recent articles. The results of this study show that children with special needs do not mean that they are not entitled to education like other normal children. Education for children with hearing and speech impairments can be done by implementing a learning environment that is tailored to their needs, for example: visual videos, picture cards, photos, and others.